รูปแบบความร่วมมือในการจัดการศึกษาขององค์กรปกครองส่วนท้องถิ่น (MODELS FOR THE COLLABORATION OF LOCAL ADMINISTRATIVE ORGANIZATIONS IN THE PROVISION OF EDUCATION) - รักษ์พลเมือง, ชนิตา; สุคนธทรัพย์, สนานจิตร; หงส์วิทยากร, อุบลวรรณ (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2015)
การจัดการศึกษาเป็นภารกิจหนึ่งที่สำคัญขององค์กรปกครองส่วนท้องถิ่น อย่างไรก็ตามปรากฏว่าองค์กรปกครองส่วนท้องถิ่นจำนวนมากโดยเฉพาะองค์กรที่มีขนาดเล็กยังไม่สามารถดำเนินการตามภารกิจนี้ได้โดยลำพัง เมื่อศึกษาการดำเนินงานในต่างประเทศที่มีนโยบายกระจายอำนาจในการจัดการศึกษาพบว่ามีความร่วมมือระหว่างองค์กรปกครองส่วนท้องถิ่นอย่างเป็นทางการหลายรูปแบบรวมถึงความร่วมมือในลักษณะสหการซึ่งประสบความสำเร็จในการจัดการศึกษาแต่ยังไม่เคยมีการนำมาใช้ในประเทศไทย ผู้วิจัยจึงได้ดำเนินโครงการวิจัยครั้งนี้โดยมีวัตถุประสงค์ (1) เพื่อสังเคราะห์รูปแบบและแนวทางการจัดการศึกษาในลักษณะความร่วมมือขององค์กรปกครองส่วนท้องถิ่นในต่างประเทศ ประกอบด้วยสาธารณรัฐฝรั่งเศส ญี่ปุ่น สหรัฐอเมริกา สหราชอาณาจักร (อังกฤษและเวลส์) และสหพันธรัฐฟินแลนด์ (2) เพื่อพัฒนารูปแบบและแนวทางความร่วมมือในการจัดการศึกษาสำหรับองค์กรปกครองส่วนท้องถิ่นในประเทศไทย การวิจัยครั้งนี้ใช้วิธีการวิจัยแบบผสมผสาน โดยการวิจัยเอกสาร การสำรวจจากแบบสอบถาม การสัมภาษณ์ การสนทนากลุ่ม และการวิจัยภาคสนาม ผลการวิจัยพบว่า ผู้บริหารองค์กรปกครองส่วนท้องถิ่นส่วนใหญ่ให้การสนับสนุนงบประมาณเพื่อการศึกษา และผู้บริหารเกือบทั้งหมดเห็นว่ามีความจำเป็นต้องดำเนินภารกิจโดยอาศัยความร่วมมือในการจัดการศึกษา โดยเฉพาะการศึกษาในระบบโรงเรียน โดยเห็นว่าควรมีความร่วมมือทั้งระหว่างองค์กรปกครองส่วนท้องถิ่นรูปแบบเดียวกัน และต่างรูปแบบจากการวิจัยภาคสนาม 12 จังหวัด พบว่าองค์กรปกครองส่วนท้องถิ่นในประเทศไทยมีความร่วมมือจัดการศึกษาในลักษณะต่างๆ ยกเว้นรูปแบบนิติบุคคล ผู้วิจัยจึงได้นำเสนอรูปแบบความร่วมมือจัดการศึกษาที่มีความเป็นไปได้ 5 รูปแบบ รวมทั้งความร่วมมือในรูปแบบสหการการศึกษา ที่กรมส่งเสริมการปกครองท้องถิ่น กระทรวงมหาดไทย ควรให้การสนับสนุน และเป็นรูปแบบที่มีความเป็นไปได้มากขึ้นตามหลักการรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 คำสำคัญ: ความร่วมมือจัดการศึกษา องค์กรปกครองส่วนท้องถิ่น สหการการศึกษา Provision of education is one of the important missions of the local administrative organizations; however, many organizations especially the small ones could not fulfill this mission by themselves. After reviewing countries which have policies to promote decentralization of education, it was found that there were many forms of formal collaboration between local administrative organizations, including education syndicate which was an effective model in providing education but had not been administered in Thailand. This research project was thus studied with the objectives to (1) analyze collaboration models and guidelines for the provision of education of local administrative organizations in foreign countries; namely, France, Japan, the United States, the United Kingdom (England and Wales), and Finland; and (2) to propose models and guidelines for the provision of education of local administrative organizations in Thailand. The researchers employed mixed method research consisting of document research, survey research using questionnaire, interview, focus group discussion, and field research study. Findings reviewed that most of the administrators in local administrative organizations provided budgetary support for education in the areas. Almost all of the respondents agreed that there should be collaborations among local administrative organizations in providing education, especially formal schooling. Such collaborations could be initiated between local administrative organizations of the same and different types. Evidence from field research in 12 provinces showed that local administrative organizations had some collaboration in many models except that in juristic person model. The research proposed 5 models for educational collaborations including education syndicate which should be promoted by the Department of Local Administration, Ministry of Interior and could be initiated under the principle of the Constitution of the Kingdom of Thailand, B.E. 2550 (2007). Keywords: Educational Collaboration, Local Administrative Organizations, Education Syndicate